The Role of Emotional and Meta-Emotional Intelligence in Pre-adolescents’ Well-Being and Sociometric Status - D’Amico, Antonella; Geraci, Alessandro (Frontiers in Psychology, 2021)
The study examined the relationships among emotional and meta-emotional intelligence, well-being, and sociometric status in 105 pre-adolescents. Emotional and meta-emotional intelligence were measured using the IE-ACCME test (Author, 2013), allowing to measure ability EI, emotional self-concept, meta-emotional knowledge, meta-emotional ability in self-evaluation and meta-emotional beliefs. Meta-emotional dimensions refer to the awareness of individuals about their emotional abilities and to their beliefs about the functioning of emotions in everyday life. Eudemonic well-being and sociometric status were respectively measured using the well-known PWB scale by Ryff’s (1989) and registering the levels of acceptance/rejection from peers (Moreno, 1960). Results demonstrated that: pre-adolescents’ meta-emotional beliefs are positively associated to eudemonic well-being: pre-adolescents with higher levels of ability EI, meta-emotional knowledge and meta-emotional self-evaluation are more accepted by others while those that overestimate their emotional abilities are more refused by peers. These results evidence that meta-emotional variables may play a crucial role in well-being and sociometric status, encouraging future studies on this issue.